Channel protein engineering: synthetic 22-mer peptide from the primary structure of the voltage-sensitive sodium channel forms ionic channels in lipid bilayers. - Oiki, S (1988)
A synthetic 22-mer peptide that mimics the sequence of a putative pore segment of the voltage-dependent sodium channel forms transmembrane ionic channels in lipid bilayers. Several features of the authentic sodium channel are exhibited by the synthetic peptide: (i) The single channel conductance of the most frequent event is 20 pS in 0.5 M NaCl. (ii) The single channel open and closed lifetimes are in the ms time range. (iii) The synthetic channel discriminates cations over anions but is nonselective between Na+ and K+. However, the synthetic channel displays no significant voltage dependence. Energetic considerations suggest a bundle of four parallel amphipathic alpha-helices as the most plausible channel structure. The synthetic 22-mer channel-forming peptide allows study of the mechanisms of ion permeation through sodium channels by protein engineering techniques.